Pushing the Envelope in Paradise: A Novel Approach to Rat Eradication at Palmyra Atoll - Wegmann, Alexander; Flint, Elizabeth; White, Susan; Fox, Mark; Howald, Gregg; McClelland, Pete; Alifano, Aurora; Griffiths, Richard (Proceedings of the Vertebrate Pest Conference, 2012)
Palmyra Atoll National Wildlife Refuge is a moist Central Pacific atoll that supports one of the best remaining tropical forest ecosystems in the region, including 10 species of breeding seabirds and a robust population of the world’s largest terrestrial invertebrate, the coconut crab. Despite these riches, the atoll’s ecosystem has been modified by introduced black rats that were inadvertently brought to Palmyra during WWII. Between June 1 and 30, 2011, a partnership between the U.S. Fish and Wildlife Service, The Nature Conservancy, and Island Conservation successfully implemented a project to remove rats from Palmyra. Independent monitoring of bait application and its environmental effects was undertaken by the USDA. Over the 28-day operation, a team of 41 people from 5 countries utilized 2 helicopters, 10 slingshots, 148 bait stations, and hand spreading to strategically apply 38,561 kg of rodent bait containing the anticoagulant brodifacoum (25 ppm) to Palmyra’s 235 hectares of emergent land. Palmyra’s challenging eradication environment demanded the development of a novel approach, such as broadcast application rates between 75 and 85 kg/ha and the use of “bolas” to bait coastal forest canopy to minimize bait drift into the marine environment. Initial findings show minimal non-target impacts as a result of the project, and post-eradication monitoring has failed to detect rats. Increased recruitment by at least 2 native tree species has been observed. By removing rats from Palmyra, the partnership aims to safeguard the atoll’s indigenous flora and fauna, encourage the reestablishment of extirpated seabird species, and create an ecological refuge for species within the Central Pacific region that are at risk of extinction. This project is a conservation milestone for the Refuge, and it has established a benchmark for eradication campaigns on other tropical islands.